Lower baseline testosterone level is related to earlier development of castration resistance in metastatic prostate cancer: a multi-center cohort study - Wong, Ho Ming Chris; Chiu, Peter Ka-Fung; Puche-Sanz, Ignacio; Xue, Zhao; Chen, Dong-Ning; Gomez-Gomez, Enrique; Heidegger, Isabel; Kafka, Mona; Wei, Yong; Sakamoto, Shinichi; Ng, Anthony Chi Fai (Frontiers in Oncology, 2024)
In the era of concurrent combination therapy in metastatic hormone sensitive prostate cancer, the impact of the testosterone level before initiating androgen deprivation therapy on treatment outcome is still uncertain. We aimed to investigate its effect on time-to-castration-resistence in a metastatic hormone sensitive prostate cancer cohort.This is a multi-centre retrospective study of 5 databases from China, Japan, Austria and Spain including 258 metastatic hormone sensitive prostate cancer patients with androgen deprivation therapy initiated between 2002 and 2021.Baseline testosterone was divided into high and low groups using 12 nmol/L as cutoff level.Primary outcome was time-to-castration-resistence. Secondary outcomes were survival functions. Kaplan-Meier method was employed to evaluate the correlation between baseline testosterone and time-to-castration-resistence. Subgroup analysis was performed to elucidate the effect of upfront combination-therapy and metastatic volume.Median age was 72 years. Median follow-up time was 31 months. Median pre-treatment prostate-specific-antigen level was 161 ng/mL. Majority of case were graded as International-Society-of-Urological-Pathology grade 5 (63.6%). 57.8% patients had high volume disease and 69.0% received upfront combination treatment. 44.6% of the cohort developed castrationresistence. The low testosterone group demonstrated shorter mean-time-to-castrationresistence (19.0 vs 22.4 months, p=0.031). The variance was more significant in patients without combination therapy (13.2 vs 26.3 months, p=0.015). Cancer-specific and overall survival were inferior in the low baseline testosterone level group without receiving combination therapy (p=0.001).Lower pre-treatment testosterone level is correlated to shorter time-to-castration resistence and worse survival in metastatic prostate cancer patients without upfront combination therapy.